Relationship of epilepsy on the linguistic-cognitive profile of children with ASD: A systematic review of the literature - Cano-Villagrasa, Alejandro; Moya-Faz, Francisco José; López-Zamora, Miguel (Frontiers in Psychology, 2023)
Introduction The prevalence of comorbidity between epilepsy and Autism Spectrum Disorder (ASD) in the pediatric age increased significantly in recent years. The onset of epilepsy negatively influences the abilities of the user with ASD. Thus, epilepsy will be a disabling factor that will reduce the cognitive-linguistic skills of users with ASD. The main objective of this work is to review the current scientific literature and to compare the relationship of epilepsy on the development of cognitive and linguistic skills of children with ASD. Methods In this regard, a systematic search was carried out in the main sources (Medline, PubMed, WOS, ResearchGate and Google Scholar). 481 articles were identified, from which, after meeting the different inclusion and exclusion criteria, a total of 18 studies of relevance to the objectives of this work were selected. Results The results reflect that, at a global level, epilepsy significantly influences the performance of cognitive- linguistic skills in people with ASD. Discussion In conclusion, epilepsy in the ASD population leads to a reduction in cognitive and linguistic abilities, which respond to the different types of epilepsy and their location, significantly impacting the quality of life and basic activities of daily living of the user with ASD.